If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 4) = -3(5x + -3) Reorder the terms: 2(4 + 2x) = -3(5x + -3) (4 * 2 + 2x * 2) = -3(5x + -3) (8 + 4x) = -3(5x + -3) Reorder the terms: 8 + 4x = -3(-3 + 5x) 8 + 4x = (-3 * -3 + 5x * -3) 8 + 4x = (9 + -15x) Solving 8 + 4x = 9 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 8 + 4x + 15x = 9 + -15x + 15x Combine like terms: 4x + 15x = 19x 8 + 19x = 9 + -15x + 15x Combine like terms: -15x + 15x = 0 8 + 19x = 9 + 0 8 + 19x = 9 Add '-8' to each side of the equation. 8 + -8 + 19x = 9 + -8 Combine like terms: 8 + -8 = 0 0 + 19x = 9 + -8 19x = 9 + -8 Combine like terms: 9 + -8 = 1 19x = 1 Divide each side by '19'. x = 0.05263157895 Simplifying x = 0.05263157895
| -4(x-8)-7=7(x-6) | | 6(x+2)-8=4x+2(1+x) | | 6x-8=4x+18 | | (9x+20)=28 | | 8-5(x+3)=x-29 | | 105=15+18v | | 3(x+5)-4=6x-3(-4+x) | | 10b+-2=7b-7.4 | | x=31.64165854+-1.536585366y | | (12a-3b-5c)-5(-5a+4b-6c)= | | -23.4/_1/3 | | (x+3)(6x-8)= | | 2x+75=6x-1 | | .16(x-5)=.50(x+6) | | f(x)=x^5+3x^4-2x^2+4x-7 | | 5X^2+3X-X=0 | | 9x-6+9x+5=9x+9x-4 | | (2x-4)=x+61 | | 9.3m+7.8-2.3m=-9.6+7m+17.4 | | x*4=212 | | 1/6(x-5)=1/2(x=6) | | -5x+2(3x-6)=-7-4x | | 2x+4+x+8=5x+2 | | 8x-(3x+3)=6x-17 | | q^3*p^3=35 | | 23x=13 | | 7x-6=8(x+4) | | 3(x+1)=-2(2x+2) | | h(-3)+8=-2x-5 | | 4.5m+7.4-7m=-1.3-2.5m+8.7 | | -2x+7(-3x-7)=-69-3x | | 4x+8+8x+9=9x+3x+14 |